The Effect of Lecturer Professionalism and Quality of Academic-Administrative Services on Student Satisfaction with The Mediation of Student Comfort At STIT Pringsewu - Diena Izzaty Muslih; Zainul Kisman (Goodwood Publishing, 2026)
Purpose: This study aimed to examine the effects of lecturer professionalism and academic–administrative service quality on student satisfaction, with student comfort serving as a mediating variable at STIT Pringsewu. Research Methodology: This study used a quantitative approach with a cross-sectional design. Primary data were collected through questionnaires administered to active undergraduate students in Semesters 4 and 6. A purposive sampling technique was used with 347 respondents from a population of 2,619 students. Data analysis was performed using Partial Least Squares structural equation modeling (PLS-SEM). Results: The results showed that lecturer professionalism and academic–administrative service quality significantly affect student satisfaction, both directly and indirectly through student comfort as a mediating variable. The endogenous construct